Influence of the lactokinin Ala-Leu-Pro-Met-His-Ile-Arg (ALPMHIR) on the release of endothelin-1 by endothelial cells - Maes, Wim; Van Camp, John; Vermeirssen, Vanessa; Hemeryck, Mattias; Ketelslegers, Jean Marie; Schrezenmeir, Jürgen; Van Oostveldt, Patrick; Huyghebaert, André (Regulatory peptides, 2004)
Milk protein-derived peptides with angiotensin-converting enzyme (ACE) inhibitory activity can reduce blood pressure in hypertensive subjects. The lactokinin Ala-Leu-Pro-Met-His-Ile-Arg (ALPMHIR) is an ACE-inhibitory peptide released by tryptic digestion from the milk protein β-lactoglobulin. Its ACE-inhibitory activity is 100 times lower than that of captopril. The latter is known to inhibit the release of the vasoconstrictor endothelin-1 (ET-1) by endothelial cells. The effects of ALPMHIR on the endothelium are currently unknown. In this study, the influence of ALPMHIR on release of ET-1 by endothelial cells was investigated. The basal ET-1 release of the cells was reduced by 29% ( p<0.01) in the presence of 1 mM ALPMHIR, compared to 42% ( p<0.01) for 0.1 mM captopril. Addition of 10 U/ml thrombin to the incubation medium increased the release of ET-1 by 66% ( p<0.01). Co-incubation of 10 U/ml thrombin with 1 μM captopril or with 0.1 mM ALPMHIR inhibited the stimulated ET-1 release by 45% ( p<0.01) and by 32% ( p<0.01), respectively. These data indicate that dietary peptides, such as ALPMHIR, can modulate ET-1 release by endothelial cells. These effects, among other mechanisms, may play a role in the anti-hypertensive effect of milk protein-derived peptides.